Mobilidade do colo vesical após intervenção fisioterapêutica em mulheres com incontinência urinária de esforço com auxílio da ultrassonografia: ensaio clínico - SOUSA, Agda Ramyli da Silva (UNIFAP - Universidade Federal do Amapá, 2020)
The pelvic floor is essential to support the pelvic and abdominal viscera, especially the uterus, bladder and rectum. When these muscles are weak, urinary incontinence may develop and pelvic organ prolapse. Objective: To analyze the mobility of the bladder neck through ultrasound before and after a program to strengthen the pelvic floor muscles in stress urinary incontinence. Methodology: Single-blind randomized clinical trial, as an extension of the extension project “Education and health promotion of hypo-sufficient, riverside, quilombola women, indigenous people with urinary incontinence to improve the quality of life” developed at the Federal University of Amapá. The sample consisted of 9 women divided into two groups, according to randomization. Group 1 obtained manual therapy and group 2, manual therapy plus electrotherapy, both groups performed household exercises from the second week of treatment. The inclusion criteria for participation in the study were women, aged 40 to 50 years, who presented significant urinary loss through physical effort. The exclusion criteria were pregnant women, urinary tract infections, neurological diseases, total hysterectomy, pelvic tumors, metallic implant and clinical or surgical treatment for urinary incontinence, prior to the study. The treatment consisted of 16 sessions, performed twice a week, with an approximate duration of 50 minutes for both groups. Results: The results of bladder neck mobility at rest did not vary significantly between groups G1 (0.74 ± 0.26 versus 1.10 ± 0.63; p = 0.07) and G2 (1.14 ± 0.687 versus 1.47 ± 0.59; p = 0.10); before and after treatment. The same was repeated in the effort condition, G1 (0.49 ± 0.39 versus 0.67 ± 0.22; p = 0.46) and G2 (0.46 ± 0.12 versus 0.35 ± 0, 23; p = 0.46); before and after treatment. In the displacement condition, there was no significant difference between G1 (0.67 ± 0.53 versus 0.75 ± 0.40; p = 0.68) and G2 (0.68 ± 0.75 versus 1.12 ± 0.82; p = 0.14). In the follow up, the values were also insignificant; at rest G1 (1.34 ± 0.32; p = 0.13) and G2 (1.23 ± 0.42; p = 0.28). In effort G1 (0.39 ± 0.39; p = 0.13) and G2 (0.39 ± 0.24; p = 0.71). In displacement, the G1 group showed a significant difference (0.94 ± 0.34; p = 0.04); however, the G2 result was insignificant (0.92 ± 0.53; p = 0.85). Conclusion: It was concluded that 2D transvaginal ultrasound proved to be an easily reproducible technique for assessing the location of the bladder neck. After treatment, both groups showed significant improvement in the symptoms of urinary loss and quality of life. In contrast, only the G1 group achieved significant improvement in muscle strength, according to the Oxford scale; and in the elevation of the bladder neck, according to the ultrasound examination. Pelvic floor muscle training was significantly a non-surgical treatment option, capable of reducing the severity of urinary incontinence in women. However, further studies are needed to verify the mobility of the bladder neck after a program to strengthen pelvic floor muscles